Forest fire spreading and carbon concentration identification in tropical region Indonesia - Abdul Kadir, E. (Elsevier B.V., 2021)
Global warming impacted the rise of temperature globally, some of the places a high risk of fire such as land and forest fire. Many efforts to prevent the occurrence of land and forest fire, but some methods are not achieved in optimum results. One of the issues is carbon emitted to the sky is in general concentration. The current sensor only detected carbon status and without the detail of the carbon concentration either from the forest fire or any other source that contribute carbon. This research identifies and detects the fog of haze emitted from a forest fire by identifying the carbon concentration. The carbon sensor detects particles flying in the skies and calculates based on number and size to identify if the fog comes from a forest fire or other fire sources. There are many other sources of haze in the skies. It can be from the pollution emitted from vehicles, fire from the garbage or rubbish, or fog emitted from the factory. The size and number of particles detected by the sensor were analyzed to identify the quantity and the size to match the type of particles emitted from the forest fire. Results show that particles from the forest fire are higher and bigger compare to other sources of fires. The fog's intensity less than from other fire sources because of forest fire the material mostly from the trees and leaves getting burn then gives less in quantity. Â© 2021